Battery

By introducing a buffer layer between the positive electrode sheet and the solid electrolyte layer of the ultra-low liquid solid or solid state battery, the micro-short circuit problem caused by the solid electrolyte layer being pressed through or uneven during the pressing process of the battery, the high energy density and excellent electrical performance of the battery are achieved.

CN119786754AActive Publication Date: 2025-04-08QINGTAO (KUNSHAN) ENERGY DEV CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510281155.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-11
Publication Date
2025-04-08
Estimated Expiration
2045-03-11

AI Technical Summary

Technical Problem

During the pressing process of ultra-low liquid solid or solid state batteries, due to the poor mechanical properties of the solid electrolyte membrane and the high hardness of the positive electrode sheet, the solid electrolyte layer is easily pressed or uneven, resulting in a micro-short circuit, which affects the battery performance.

Method used

A buffer layer is introduced between the positive electrode sheet and the solid electrolyte layer. The buffer layer is composed of a second active material and a second solid electrolyte. The mass proportion of the second solid electrolyte is 50%-80% to achieve pressure buffering and conductive compensation.

Benefits of technology

By introducing a buffer layer, the micro-short circuit problem is solved, ensuring the high energy density and excellent electrical performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_12
    Figure SMS_12
  • Figure SMS_13
    Figure SMS_13
  • Figure SMS_16
    Figure SMS_16
Patent Text Reader

Abstract

The invention discloses a battery. The battery is formed by sequentially laminating and assembling a positive pole piece, a buffer layer, a solid electrolyte layer and a negative pole piece, wherein the positive pole piece comprises a first active material and a first solid electrolyte; the buffer layer comprises a second active material and a second solid electrolyte; the first mass ratio of the first solid electrolyte in the total amount of the first active material and the first solid electrolyte is not more than 40%, and the second mass ratio of the second solid electrolyte in the total amount of the second active material and the second solid electrolyte is 50-80%; and the ratio of the second mass ratio to the first mass ratio is greater than 1.6. The buffer layers are arranged in the positive pole piece and the solid electrolyte layer, so that the problem of micro short circuit in the existing battery is avoided, and excellent electrical performance is realized while high energy density of the battery is ensured.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of chemical energy technology, and in particular to an ultra-low liquid content solid-state or solid-state battery using a buffer layer. Background Art

[0002] With the rapid development of new energy technology, ultra-low liquid content solid-state batteries (liquid content <5%) or solid-state batteries have become one of the main directions of future energy development. Currently, ultra-low liquid content solid-state batteries or solid-state batteries are composed of a positive electrode sheet, a solid electrolyte layer (the thickness of the layer is generally ), the negative electrode sheets are stacked in order and then pressed. During the pressing process (pressure is usually > 300MPa), due to the poor mechanical properties of the solid electrolyte membrane, the high hardness of the positive electrode sheet and the inability to ensure absolute uniformity and flatness, the solid electrolyte layer is easily pressed through or uneven in various parts during the battery pressing process, resulting in micro-short circuits during the battery cycle, affecting battery performance. Summary of the invention

[0003] In order to solve the above problems, the present application discloses a battery. The battery may include an ultra-low liquid content solid-state battery or an all-solid-state battery. The battery includes a buffer layer, which can be placed between the positive electrode plate and the solid electrolyte layer, while ensuring the high energy density of the battery, solving the micro-short circuit problem and achieving excellent electrical performance.

[0004] The present application discloses a battery, which is assembled by sequentially stacking a positive electrode sheet, a buffer layer, a solid electrolyte layer, and a negative electrode sheet; wherein the positive electrode sheet includes a first active material and a first solid electrolyte; the buffer layer includes a second active material and a second solid electrolyte; the first mass proportion of the first solid electrolyte in the total amount of the first active material and the first solid electrolyte does not exceed 40%, the second mass proportion of the second solid electrolyte in the total amount of the second active material and the second solid electrolyte is 50%-80%, and the ratio of the second mass proportion to the first mass proportion is greater than 1.6.

[0005] According to some embodiments of the present application, the solid electrolyte layer includes a third solid electrolyte; the first volume average particle size of the first solid electrolyte does not exceed the second volume average particle size of the second solid electrolyte; and the second volume average particle size does not exceed the third volume average particle size of the third solid electrolyte.

[0006] According to some embodiments of the present application, a ratio of the third volume average particle size to the first volume average particle size is greater than 1.2.

[0007] According to some embodiments of the present application, the first active material is the same as or different from the second active material; the first solid electrolyte, the second solid electrolyte, and the third solid electrolyte are the same as or different.

[0008] According to some embodiments of the present application, the fourth volume average particle size of the first active material is not less than the fifth volume average particle size of the second active material.

[0009] According to some embodiments of the present application, the thickness of the buffer layer is .

[0010] According to some embodiments of the present application, the thickness of the buffer layer is not less than 5% of the thickness of the positive electrode plate and not more than 60% of the thickness of the solid electrolyte layer.

[0011] The liquid content in the battery is less than 5%; Further preferably, the liquid content is less than <1%; Further preferably, the liquid content is less than <0.01%; According to some embodiments of the present application, a ratio of a fourth volume average particle size of the first active material to a first volume average particle size of the first solid electrolyte is greater than 2.

[0012] According to some embodiments of the present application, a ratio of a fifth volume average particle size of the second active material to a second volume average particle size of the second solid electrolyte is greater than 1.2.

[0013] According to some embodiments of the present application, the positive electrode plate also includes a first conductive agent and a first binder, the buffer layer also includes a second conductive agent and a second binder, and the solid electrolyte layer includes a third binder; wherein the first conductive agent is the same as or different from the second conductive agent, and the first binder, the second binder, and the third binder are the same as or different.

[0014] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. DETAILED DESCRIPTION

[0015] In order to make the above-mentioned purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are described in detail below. In the following description, many specific details are set forth to facilitate a full understanding of the present application. However, the present application can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present application, so the present application is not limited by the specific embodiments disclosed below.

[0016] Unless otherwise defined, all technical and scientific terms used in this application have the same meaning as those commonly understood by technicians in the technical field of this application. The terms used in this application and in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application. The words "including" or "comprising" and the like used in this application mean that the elements or objects appearing before the word cover the elements or objects listed after the word and their equivalents, without excluding other elements or objects. The terms "and / or" or "and / or" used in this application include any and all combinations of one or more related listed items.

[0017] At present, in order to solve the problems in battery compression molding, the solid electrolyte layer is thickened, such as The above problems can be alleviated by reducing the positive electrode active material loading and particle size in the positive electrode sheet, but this will result in a significant loss in the battery's energy density and electrical performance.

[0018] The battery disclosed in the present application can solve related problems while ensuring the excellent electrical performance of the battery by adding a buffer layer in the positive electrode plate and the solid electrolyte layer.

[0019] Some preferred embodiments of the present application are described below. It should be noted that the following description is for the purpose of illustration and is not intended to limit the scope of protection of the present application. The steps involved in the present application can be performed accurately in sequence, or various steps can be processed in reverse order or simultaneously. At the same time, other operations can also be added to these processes, or one or more operations can be removed from these processes.

[0020] The present application discloses a battery, which may include an ultra-low liquid content solid-state battery or an all-solid-state battery. The battery may be assembled by stacking a positive electrode sheet, a buffer layer, a solid electrolyte layer, and a negative electrode sheet in sequence. The buffer layer is arranged between the positive electrode sheet and the solid electrolyte layer, and plays the role of pressure buffering and conductive compensation for the solid electrolyte layer.

[0021] It can be understood that a low-liquid solid-state battery refers to a battery with a liquid content of less than 5%, and an all-solid-state battery refers to a battery that contains essentially no liquid.

[0022] The positive electrode sheet may include a first active material and a first solid electrolyte. As an example, the first active material may include but is not limited to a layered oxide material (e.g., lithium cobalt oxide LiCoO2, nickel-cobalt-manganese ternary material LiNi x Co y Mn 1-x- y O2, nickel-cobalt-aluminum ternary material LiNi x Co y Al 1-x-yO2, etc.), spinel structure materials (for example, lithium manganese oxide LiMn2O4, high voltage nickel manganese spinel LiNi 0.5 Mn 1.5 O4, etc.), olivine structure materials (e.g., lithium iron phosphate LiFePO4, etc.), sulfur-based materials (e.g., sulfur element S, transition metal chalcogenides and their composites, etc.), conversion-type positive electrode materials (e.g., metal fluorides such as CoF2, FeF3, metal chlorides such as CoCl2, etc.), lithium-rich layered oxides (e.g., Li2MnO3·LiMO2, M=Ni, Co, Mn), polyanion compounds (e.g., phosphates, pyrophosphates, sulfates, silicates, borates and mixed polyanions, etc.) or any combination thereof. In some embodiments, the first positive electrode material may be a lithium salt, for example, the active material includes lithium cobalt oxide, lithium iron phosphate, lithium manganese oxide, lithium nickel oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium-rich manganese-based materials, etc.

[0023] The first solid electrolyte may include, but is not limited to, a polymer solid electrolyte, an inorganic solid electrolyte, a glassy and glass-ceramic electrolyte, a composite solid electrolyte, etc., or any combination thereof. Exemplary polymer solid electrolytes may include polyethylene oxide (PEO), poly(propylene oxide) (PPO), polyolefin polymer electrolytes (e.g., polyvinylidene fluoride (PVDF), poly(vinylidene fluoride-hexafluoropropylene) (PVDF-HFP), etc.), polyacrylonitrile (PAN)-based electrolytes, polymethyl methacrylate (PMMA)-based electrolytes, polyvinyl pyrrolidone (PVP)-based electrolytes, polysiloxane-based electrolytes (e.g., polydimethylsiloxane (PDMS), etc.), ionic liquid polymer electrolytes (e.g., poly(ionic liquid), etc.), etc., or any combination thereof. The above polymer solid electrolytes can be used in combination with different types of lithium salts (e.g., LiClO4, LiTFSI, LiBF4, etc.) to achieve good flexibility and high ionic conductivity.

[0024] Exemplary inorganic solid electrolytes may include oxide solid electrolytes, halide solid electrolytes, sulfide solid electrolytes, etc. Among them, oxide solid electrolytes may include but are not limited to garnet-type solid electrolytes such as LLZO, LLTO, LBLTO, etc. or element replacement, NASICON-type solid electrolytes such as LTPA, LAGP, etc. or their element replacement, Li3xLa (2 / 3)-x TiO3、Li 0.34 La 0.51 TiO 2.94 Perovskite solid electrolytes such as Li3OCl, Li3OBr, etc. or their element substitution bodies, antiperovskite oxide electrolytes such as Li 14 ZnGe4O 16, Li4SiO4, LiGeO4 or their element substitution bodies, LISICON-type solid electrolytes such as Li3BO3, Li2B4O7 or their element substitution bodies, borate oxide electrolytes such as LLZO-LLTO, LATP-LLZO or other composite oxide electrolytes, or Li3PO4 or its N substitution bodies, etc., one or more. Optionally or preferably, the inorganic oxide may include one or more of LLZO, LLTO, LAGP, LATP, LBSPO, LPO, Li4SiO4, Li2ZnTi3O8, and / or one or more of their derivatives. The halide solid electrolyte may be of the chemical formula Li a MX b Indicates that M represents a metal element or a metalloid element, and X represents a halogen element. Among them, "metalloid element" can represent an element with similar metal properties, and can include B, Si, Ge, As, Sb, Te, etc. Optionally or preferably, M can include but is not limited to Al, Zn, Mg, Ca, Ba, Mn, Zr, Cd, Co, Yb, Y, Cr, In, Ga, Sr, Hf, Ti, Ta, Sn, Nb, Er, Sc, etc. or any combination thereof. In some embodiments, M can be one or more of Y, In or Zr. For example, the halide solid electrolyte can be a Zr-based halide solid electrolyte, including Li2ZrCl6, Li3Zr2I9, Li2ZrI6, etc. For another example, the halide solid electrolyte can be an In-based halide solid electrolyte, including Li3InCl6, Li3InBr6, Li3InI6, Li3In2Cl9, etc. For example, the halide solid electrolyte can be a Y-based halide solid electrolyte, including Li3YCl6, Li3YBr6, Li3YI6, Li3Y(Cl 1-x Br x )6, etc. M and X in the above halide solid electrolytes can each contain two or more elements to form a mixed halide electrolyte. For example, Li2ZrCl 6-x Br x , Sulfide solid electrolytes can include but are not limited to lithium sulfide series (Li2S-P2S5 system, such as LGPS, Li7P3S 11 , Li3PS4, etc.), germanium sulfide series (such as LGPS, LSPS, etc.), tin sulfide series (for example, Li4SnS4, etc.), lithium boron sulfide series (for example, Li3BS3, etc.), sulfur halide series (for example, Li6PS5X, Li3InX6, etc., X = Cl, Br, I), etc. or any combination thereof. Optionally or preferably, the sulfide solid electrolyte may include one or more of Li6PS5Cl, Li2S-P2S5, LGPS, etc.

[0025] Exemplary glassy and glass-ceramic electrolytes may include, but are not limited to, Li2O-B2O3-SiO2 systems, Li2S-P2S5 systems, LiF-AlF3 systems, Li2O-Al2O3-TiO2-P2O5 systems, Li2O-SiO2-P2O5 systems, 70Li2S·30P2S5 glass-ceramic, Li2S-P2S5-LiI systems, Li2S-P2S5-P2S3 systems, Li2O-B2O3-P2O5 systems, Li2O-Al2O3-GeO2-P2O5 systems, Li 1+x Al x Ti 2-x (PO4)3、Li 10 GeP2S 12 , Li3PS4-LiI composite electrolyte, Li2S-P2S5-LiBH4 system, etc., or any combination of multiple electrolytes.

[0026] Exemplary composite solid electrolytes may include inorganic-polymer composite electrolytes, inorganic-inorganic composite electrolytes, polymer-polymer composite electrolytes, ternary composite electrolytes, and functional composite electrolytes. Among them, inorganic-polymer composite electrolytes may include ceramic-filled polymer electrolytes such as PEO-LLZO, PEO-LAGP, etc., polymer-enhanced ceramic electrolytes such as LLZO-PEO, LATP-PEO, etc., polymer-coated ceramic electrolytes such as LGPS-PEO, etc. Inorganic-inorganic composite electrolytes may include oxide-oxide composite electrolytes such as LLZO-LATP, etc., sulfide-oxide composite electrolytes such as Li 10 GeP2S 12 -Li3BO3, etc., halide-oxide composite electrolytes such as LiF-Li3YCl6, etc. Polymer-polymer composite electrolytes may include PEO-PVDF composite electrolytes, PEO-PAN composite electrolytes, PEO-PMMA composite electrolytes, etc. Ternary composite electrolytes may include polymers, ceramics, lithium salt ternary polymers such as PEO-LLZO-LiTFSI, polymers, inorganic fillers, lithium salt ternary polymers such as PAN-SiO2-LiClO4, copolymers, ceramics, lithium salt ternary polymers such as PVDF-HFP-Al2O3-LiTFSI, etc. Functionalized composite electrolytes may include surface-modified LLZO-PEO composite electrolytes, cross-linked PEO-ceramic composite electrolytes, ionic liquid enhanced composite electrolytes, etc.

[0027] The above first solid electrolyte can also be modified, doped, composited, etc. to improve the physical and chemical properties, including improving stability and mechanical strength, improving ionic conductivity, etc. For example, coating a conductive polymer or a protective layer on the surface of the first solid electrolyte, doping with other metal elements such as Al, Mg, Ca, etc., reusing two or more first solid electrolytes, or composited with carbon nanotubes (CNTs) or graphene, etc.

[0028] In some embodiments, the mass proportion of the first solid electrolyte in the total mass of the first active material and the first solid electrolyte (referred to as the first mass proportion in this application, denoted as w1) does not exceed 40%. Optionally or preferably, the first mass proportion does not exceed 34%. Optionally or preferably, the first mass proportion does not exceed 28%. Optionally or preferably, the first mass proportion does not exceed 22%. Optionally or preferably, the first mass proportion does not exceed 18%. Optionally or preferably, the first mass proportion does not exceed 10%. Alternatively, the first mass proportion can be any value in the above numerical range, such as 18%, 28%, etc.

[0029] The buffer layer may include a second active material and a second solid electrolyte. In some embodiments, the second active material may also be selected from one or more of the first active materials as described above. That is, the second active material may be the same as or different from the first active material. For example, the second active material may be consistent with the first active material, both being layered oxide materials such as the nickel-cobalt-manganese ternary material LiNi x Co y Mn 1-x-y O2. Alternatively, the second active material may be lithium cobalt oxide, while the first active material is still the above nickel-cobalt-manganese ternary material. The same or similar, the second solid electrolyte may also be one or more of the first solid electrolytes as described above. The two may also be the same or different. For example, the first solid electrolyte and the second solid electrolyte are both Li2ZrCl6. Alternatively, the first solid electrolyte is Li2ZrCl6, and the second solid electrolyte is LLTO. This application does not limit the selection of the above components.

[0030] In some embodiments, the mass proportion of the second solid electrolyte in the total mass of the second active material and the second solid electrolyte (referred to as the second mass proportion in this application, denoted as w2) is 50%-80%. Optionally or preferably, the second mass proportion is 55%-75%. Optionally or preferably, the second mass proportion is 60%-70%. Optionally or preferably, the second mass proportion is 62%-68%. Optionally or preferably, the second mass proportion is 64%-66%. Alternatively, the second mass proportion can be any value in the above numerical range, such as 50%, 60%, 70%, 80%, etc.

[0031] In some embodiments, the ratio w2 / w1 of the second mass proportion to the first mass proportion may be greater than 1.6. For example, the ratio w2 / w1 may be 1.7, 1.8, 1.9, 2.0, 2.2, 2.4, 2.6, 2.8, 3.0, 3.5, 4.0, 5.0, etc. or more. The ratio w2 / w1 may also be any value within the above numerical range, such as 1.79, 2.14, 2.17, 2.86, 3.33, etc.

[0032] The solid electrolyte layer may include a third solid electrolyte. The same or similar, the third solid electrolyte may be one or more of the first solid electrolyte or the second solid electrolyte as described above. That is, the first solid electrolyte, the second solid electrolyte and the third solid electrolyte may be the same or different. For example, completely different, two identical, or completely consistent. For example, all three may be Li2ZrCl6. Alternatively, the first solid electrolyte and the second solid electrolyte are both Li2ZrCl6, and the third solid electrolyte is Li6PS5Cl. Alternatively, the first solid electrolyte is Li2ZrCl6, the second solid electrolyte is LLTO, and the third solid electrolyte is Li6PS5Cl. This application does not specifically limit the selection of the above three solid electrolytes.

[0033] The above-mentioned various active materials (including the first active material and the second active material) and solid electrolytes (including the first solid electrolyte, the second solid electrolyte and the third solid electrolyte) can be in a granular form to participate in the composition of their respective corresponding components (for example, the positive electrode plate, the buffer layer, and the solid electrolyte layer). In terms of the volume average particle size Dv50, the first volume average particle size of the first solid electrolyte (denoted as DE1) may not exceed the second volume average particle size of the second solid electrolyte (denoted as DE2), and the third volume average particle size of the third solid electrolyte (denoted as DE3) may not be less than the second volume average particle size of the second solid electrolyte. In addition, the fourth volume average particle size of the first active material (denoted as DC1) may not be less than the fifth volume average particle size of the second active material (denoted as DC2). The size relationship between the above related parameters can be expressed as: DE1≤DE2≤DE3, DC1≥DC2.

[0034] At the same time, among the above-mentioned multiple parameters, the ratio DC1 / DE1 between the fourth volume average particle size DC1 of the first active material of the positive electrode sheet and the first volume average particle size DE1 of the first solid electrolyte may be greater than 2. For example, the ratio DC1 / DE1 may be 2.3, 2.6, 2.9, 3.3, 3.6, etc. or even greater. The ratio DC1 / DE1 may also be any value within the above-mentioned numerical range, such as 3.33, etc. The ratio DC2 / DE2 between the fifth volume average particle size DC2 of the second active material of the buffer layer and the second volume average particle size DE2 of the second solid electrolyte may be greater than 1.2. For example, the ratio DC2 / DE2 may be 1.3, 1.5, 2.0, 2.5, 3.0, 3.5, etc. or even greater. The ratio DC1 / DE1 may also be any value within the above-mentioned numerical range, such as 1.5, 2.0, 3.33, etc. The ratio DE3 / DE1 between the third volume average particle size DE3 of the third solid electrolyte related to the solid electrolyte layer and the first average particle size DE1 of the first solid electrolyte can be greater than 1.2. The ratio DC1 / DE1 can also be any value greater than 1.2, such as 1.67. By selecting the particle size of each component, the mechanical strength and ion conductivity of the positive electrode sheet, the buffer layer and the solid electrolyte layer can be improved / optimized, thereby improving the structural stability and electrical performance of the battery.

[0035] In some embodiments, the positive electrode plate may further include a first conductive agent and a first binder, the buffer layer may further include a second conductive agent and a second binder, and the solid electrolyte layer may further include a third binder. Among them, the above conductive agent may be one or more selected from metal conductive agents, carbon-based conductive agents, inorganic crystalline conductive agents, polymer conductive agents, etc. Exemplary metal conductive agents may include metal powders (such as aluminum powder, nickel powder, etc.), metal fibers or metal compound fibers, etc. Exemplary carbon-based conductive agents may include graphene, carbon nanofibers (VGCF), carbon nanotubes (including single-walled carbon nanotubes (SWCNTs) and multi-walled carbon nanotubes (MWCNTs)), carbon black (such as acetylene black, etc.), amorphous carbon, etc. Exemplary inorganic crystalline conductive agents may include oxide conductive agents such as lithium oxide, aluminum oxide, magnesium oxide, etc., sulfide conductive agents such as lithium sulfide, germanium sulfide, etc., phosphate conductive agents such as lithium phosphate, fluoride conductive agents such as lithium fluoride, etc. Exemplary polymer conductive agents may include polyethylene oxide (PEO), polyvinylidene fluoride (PVDF), polyaniline (PANI), polypyrrole (PPY), polythiophene (PT), poly(3,4-ethylenedioxythiophene): polystyrene sulfonate (PEDOT:PSS), polyacrylonitrile (PAN), etc. Alternatively, any known or commercially available conductive agent may also be applicable to the present application. The first conductive agent and the second conductive agent may be selected from one or more of the aforementioned examples, respectively. The above two may be the same or different.

[0036] Any known binder includes but is not limited to polyvinylidene fluoride, polytetrafluoroethylene, polyethylene, polypropylene, aramid resin, polyamide, polyimide, polyamideimide, polyacrylonitrile, polyacrylic acid, polymethyl acrylate, polyethyl acrylate, polyhexyl acrylate, polymethacrylic acid, polymethyl methacrylate, polyethyl methacrylate, polyhexyl methacrylate, polyvinyl acetate, polyvinyl pyrrolidone, polyether, polyether sulfone, polyhexafluoropropylene, styrene-butadiene rubber, carboxymethyl cellulose, etc. or any combination thereof can be used for the present application. Copolymers can also be used as binders, and exemplary ones can be copolymers of two or more materials selected from tetrafluoroethylene, hexafluoroethylene, hexafluoropropylene, perfluoroalkyl vinyl ether, vinylidene fluoride, trifluorochloroethylene, ethylene, propylene, pentafluoropropylene, fluoromethyl vinyl ether, acrylic acid, hexadiene, etc. Alternatively, a mixture of two or more materials in the above examples can also be used as a binder. Including the first binder, the second binder and the third binder can each be selected from one or more of the above examples. The above three can also be the same or different.

[0037] The positive electrode sheet also includes a current collector for collecting and conducting electrons. The positive electrode sheet can be obtained by composite pressing the positive electrode film made of the above materials and the current collector. The current collector can be, for example, aluminum foil, nickel foil, stainless steel foil, etc.

[0038] The negative electrode plate can be a metal plate or an alloy plate, such as a lithium metal negative electrode plate or an alloy plate of metals such as lithium, tin, aluminum, germanium, and indium. The negative electrode plate can also be a silicon-based negative electrode plate, a carbon-based negative electrode plate, a metal oxide negative electrode plate, a composite material negative electrode plate, etc. Alternatively, the negative electrode plate can also be prepared using a solid electrolyte, such as one or more of the aforementioned solid electrolytes combined with an active material, or mixed with lithium metal, silicon, graphite, etc. This application does not limit the choice of the negative electrode plate.

[0039] It should be noted that the above examples of the components constituting the battery are only for illustrative purposes and are not intended to limit the protection scope of the technical solution of the present application. Any binder obtained by adjustment / modification / update without violating the inventive concept of the present application is within the protection scope of the present application.

[0040] The components of the battery can be in the form of layers, films, or blocks, and finally stacked together to form the battery. The thickness of the buffer layer can be Alternatively or preferably, the thickness of the buffer layer may be Alternatively or preferably, the thickness of the buffer layer may be Alternatively or preferably, the thickness of the buffer layer may be Alternatively, the thickness of the buffer layer can be any value within the above numerical range, for example , , Etc. In addition, the thickness of the buffer layer (recorded as T2) may be no less than 5% of the thickness of the positive electrode sheet (recorded as T1), and no more than 60% of the thickness of the solid electrolyte layer (recorded as T3). That is, 5%T1≤T2≤60%T3. Setting a reasonable buffer layer thickness can avoid the battery energy density being reduced and electrical performance being lost due to being too thin, and the battery energy density being reduced and electrical performance being lost due to being too thick.

[0041] Each component of the battery can be prepared by a known preparation method, including but not limited to wet coating, dry pressing, 3D printing, solution casting, thin film deposition, colloidal electrospinning, etc. Among them, the buffer layer can be compositely formed based on the positive electrode sheet or the solid electrolyte layer, or it can be formed separately. For example, the raw materials for preparing the buffer layer (including active materials, solid electrolytes, conductive agents, binders, etc. weighed in proportion) can be mixed in a solvent to form a slurry, and then evenly coated on the prepared positive electrode sheet or solid electrolyte layer. After drying, the solvent is removed and compacted to obtain a composite of the buffer layer and the positive electrode sheet or solid electrolyte layer. For another example, the above raw materials can be put into a mixer for mixing, and after mixing evenly, they are pressed such as direct pressing, hot pressing, extrusion, rolling, etc. to obtain a separate buffer layer. Subsequently, the positive electrode sheet, solid electrolyte layer, and negative electrode sheet are compositely pressed to obtain the battery.

[0042] The present application is further described in detail below in conjunction with the examples. It should be noted that the following examples are only used to illustrate the present application and are not used to limit the scope of protection claimed in the present application.

[0043] Example 1 - Preparation of a battery 1) Preparation of positive electrode sheet: The NCM811 positive electrode, Li2ZrCl6, and VGCF conductive agent were weighed in a ratio of 70:28:1.5 and then put into a small high-speed mixer for mixing for 30 minutes, and then 0.5% PTFE adhesive was added and continued to mix at high speed for 10 minutes for mixing and pre-fiberization. The mixture was taken out and poured into a differential roller for film formation and thinned to the target thickness, and then it was composited with aluminum foil to obtain a positive electrode sheet; 2) Preparation of buffer layer: The NCM811 positive electrode, Li2ZrCl6, and VGCF conductive agent were weighed in a ratio of 38:60:1.5 and then put into a small high-speed mixer for mixing for 30 minutes, and then 0.5% PTFE adhesive was added and continued to mix at high speed for 10 minutes for mixing and pre-fiberization, and the mixture was taken out and poured into a differential roller for film formation and thinned to the target thickness, thereby obtaining a buffer layer; 3) Preparation of solid electrolyte membrane: Li6PS5Cl and PTFE adhesive were weighed in a ratio of 99:1 and placed in a small high-speed mixer for shear mixing. After mixing evenly, the mixture was taken out and repeatedly ground in a mortar until it was in a dough (block) shape. The dough-like mixture was rolled on a differential roller press for multiple times, with a roller temperature of 80°C and a speed ratio of 3:1, to obtain a dry sulfide electrolyte membrane of the target thickness; 4) Preparation of negative electrode sheet: Li sheet and In sheet are composite pressed at a mass ratio of 1:30 to form LiIn alloy sheet; 5) Battery assembly: Cut the above-mentioned composite positive electrode sheet, buffer layer, electrolyte membrane, and negative electrode sheet into pieces according to the battery model of 20×20mm, and stack them in the order of negative electrode sheet-solid electrolyte membrane-buffer layer-positive electrode sheet, then put them into aluminum-plastic film for vacuum packaging, and finally put the packaged battery into an isostatic press for pressing at a pressure of 500MPa.

[0044] Example 2 - Preparation of a battery Compared with Example 1, Example 2 differs in that the thickness of the prepared buffer layer is different.

[0045] Example 3 - Preparation of a battery The difference between Example 3 and Example 1 and Example 2 is that the thickness of the prepared buffer layer is different.

[0046] Example 4 - Preparation of a battery The difference between Example 4 and Example 1 is that the particle size of the solid electrolyte constituting the buffer layer is different.

[0047] Example 5 - Preparation of a battery Compared with Example 1, Example 5 is different in that the particle size of the solid electrolyte constituting the buffer layer and the particle size of the active material are different.

[0048] Example 6 - Preparation of a battery Compared with Example 5, Example 6 differs in that the proportion of the solid electrolyte in the positive electrode plate is different.

[0049] Example 7 - Preparation of a battery The difference between Example 7 and Example 5 is that the proportion of the solid electrolyte in the buffer layer is different.

[0050] Example 8 - Preparation of a battery The difference between Example 7 and Example 5 is that the proportion of the solid electrolyte in the buffer layer is different.

[0051] Comparative Example 1 - Preparation of a battery Compared with Example 1, Comparative Example 1 differs in that no buffer layer is added.

[0052] Table 1 and Table 2 show the relevant parameters of the above embodiments and comparative examples.

[0053] Table 1 Particle size and thickness parameters

[0054] Table 2 Mass proportion, mass ratio and particle size ratio

[0055] Example 9 - Battery Cycle Performance Test Take the embodiment The battery obtained in Comparative Example 1 was connected to a blue power test cabinet for charge and discharge tests. The test temperature was 55°C, the voltage range was 2.0-3.65V, the charge and discharge rate of the first cycle was 0.1C, and the charge and discharge rate was 0.3C from the second cycle. After 50 cycles, the discharge capacity of the 50th cycle was divided by the discharge capacity of the second cycle to obtain the cycle capacity retention rate. The test results are summarized in Table 3.

[0056] Example 10 - Energy Density VED Calculation Based on the example The first cycle charge and discharge results of the blue battery test of the battery obtained in Comparative Example 1 are as follows: the energy value of the first cycle discharge is read as E in the blue battery test; the volume of the part of the single-layer soft-pack battery excluding the aluminum-plastic film package is measured as V; and VED=E / V is calculated. The calculation structure is summarized in Table 3.

[0057] Table 3 Energy density and cycle retention rate

[0058] It can be seen from Table 3 that, compared with Comparative Example 1, the batteries in Examples 1-8 increase the energy density of the battery by adding a buffer layer between the positive electrode sheet and the solid electrolyte layer, and increase the cycle capacity retention rate by nearly 10%. The use of a buffer layer in the battery provided in the present application not only ensures the high energy density of the battery, but also achieves excellent electrical performance.

[0059] The present application has described the basic concepts. Obviously, for those skilled in the art, the above detailed disclosure is only for example and does not constitute a limitation of the present application. Although not explicitly stated herein, those skilled in the art may make various modifications, improvements and amendments to the present application. Such modifications, improvements and amendments are suggested in the present application, so such modifications, improvements and amendments still belong to the spirit and scope of the exemplary embodiments of the present application.

[0060] At the same time, the present application uses specific words to describe the embodiments of the present application. For example, "one embodiment", "an embodiment", and / or "some embodiments" refer to a certain feature, structure or characteristic related to at least one embodiment of the present application. Therefore, it should be emphasized and noted that "one embodiment" or "an embodiment" or "an alternative embodiment" mentioned twice or multiple times in different positions in the present application does not necessarily refer to the same embodiment. In addition, some features, structures or characteristics in one or more embodiments of the present application can be appropriately combined.

[0061] Similarly, it should be noted that in order to simplify the description of the disclosure of this application and thus help understand one or more embodiments of the invention, in the above description of the embodiments of this application, multiple features are sometimes combined into one embodiment or its description. However, this disclosure method does not mean that the features required by the object of this application are more than the features mentioned in the claims. In fact, the features of the embodiments are less than all the features of the single embodiment disclosed above.

[0062] Finally, it should be understood that the embodiments described in this application are only used to illustrate the principles of the embodiments of the present application. Other variations may also fall within the scope of the present application. Therefore, as an example and not a limitation, the alternative configurations of the embodiments of the present application may be considered to be consistent with the teachings of the present application. Accordingly, the embodiments of the present application are not limited to the embodiments explicitly introduced and described in the present application.

Claims

1. A battery, characterized in that: The battery is assembled by stacking the positive electrode sheet, the buffer layer, the solid electrolyte layer, and the negative electrode sheet in sequence; wherein, The positive electrode plate includes a first active material and a first solid electrolyte; The buffer layer includes a second active material and a second solid electrolyte; A first mass proportion of the first solid electrolyte in the total amount of the first active material and the first solid electrolyte does not exceed 40%, a second mass proportion of the second solid electrolyte in the total amount of the second active material and the second solid electrolyte is 50%-80%, and a ratio of the second mass proportion to the first mass proportion is greater than 1.

6.

2. The battery according to claim 1, characterized in that The solid electrolyte layer includes a third solid electrolyte; The first volume average particle size of the first solid electrolyte does not exceed the second volume average particle size of the second solid electrolyte; and the second volume average particle size does not exceed the third volume average particle size of the third solid electrolyte.

3. The battery according to claim 2, characterized in that A ratio of the third volume average particle diameter to the first volume average particle diameter is greater than 1.

2.

4. The battery according to claim 2, characterized in that The first active material is the same as or different from the second active material; the first solid electrolyte, the second solid electrolyte, and the third solid electrolyte are the same as or different.

5. The battery according to claim 1, characterized in that A fourth volume average particle size of the first active material is not smaller than a fifth volume average particle size of the second active material.

6. The battery according to claim 1, characterized in that The thickness of the buffer layer is .

7. The battery according to claim 1, characterized in that The thickness of the buffer layer is not less than 5% of the thickness of the positive electrode plate and not more than 60% of the thickness of the solid electrolyte layer.

8. The battery according to claim 1, characterized in that A ratio of a fourth volume average particle size of the first active material to a first volume average particle size of the first solid electrolyte is greater than 2.

9. The battery according to claim 1, characterized in that A ratio of a fifth volume average particle size of the second active material to a second volume average particle size of the second solid electrolyte is greater than 1.

2.

10. The battery according to claim 1, characterized in that The positive electrode plate also includes a first conductive agent and a first binder, the buffer layer also includes a second conductive agent and a second binder, and the solid electrolyte layer includes a third binder; wherein the first conductive agent is the same as or different from the second conductive agent, and the first binder, the second binder, and the third binder are the same as or different.

Citation Information

Patent Citations

  • Dry-method positive pole piece, lithium ion battery and preparation method of dry-method positive pole piece

    CN116581249A

  • All-solid-state double-layer composite positive electrode, preparation method thereof and lithium ion battery

    CN118198335A

  • Solid state electrolyte cell and method for producing same

    CN1219779A